Las representaciones del cambio religioso en la élite dirigente argentina (1862-1916) - Di Stefano, Roberto (El Colegio de México, A.C., 2025)
This article traces and analyzes representations of the Argentine ruling elite in terms of developments on the religious terrain, in the country and in the world, from 1862 to 1916. The chronological starting point is the year of national unification and the end point that of the election of President Hipólito Yrigoyen through universal male vote, secret and obligatory. These are the decades that Argentine historiography understands as the period of national organization (1862-1880) and of conservative order (1880-1916). The sources used include parliamentary debates and the annual reports of the Department of Worship, which formed part of the Ministry of Justice, Worship and Public Instruction until 1899 and part of the Ministry of Foreign Affairs after that date. The speeches of these ministers and parliamentarians allow us to understand their diagnostics of the transformations underway and the meanings they assigned to certain political concepts that were closely connected to the religious question, such as sovereignty, democracy, nation and citizenry.